Advisory Opinion of the Caribbean Court of Justice in Response to a Request from the Caribbean Community (Caribbean Ct. J.). (August 2020) - Vasciannie, Stephen
Abstract : An Appellate Jurisdiction, which addresses municipal law cases on appeal from countries which accept this jurisdiction. To date, four Caribbean countries—Barbados, Guyana, Belize and Dominica—have accepted the appellate jurisdiction of the Court. The applicable law for each case under the appellate jurisdiction is the national law of the state from which the appeal emanates. The CCJ in its Appellate Jurisdiction is intended to replace the Judicial Committee of the Privy Council as the final court of appeal for Caribbean countries which were formerly British colonies.